The role of Job Fairs as recruitment tool - Neu, Lukáš; Semenenko, Vadim; Chvátalová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The labor market has undergone profound changes throughout history. New ways for students to find their first workplace are emerging. The aim of this thesis is to find out how efficient the job fair events are, in terms of finding new employment opportunities. This study further aims to explore the changes and overall historical evolution of labor markets ranging from the ancient Roman Empire to modern crises, e.g., 2008 financial downturn or the impact of COVID-19 pandemic. This paper examines the connection between job fair events and the labor market, while delving into crucial moments that shaped the employment dynamics into the form we know it today. By analyzing collected data, this study aims to determine how efficient the job fair events are in terms of looking for employment as students today.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses